The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/nprot.2007.318
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of DNA from small amounts of elephant ivory

Abstract: This protocol describes a method for the extraction of DNA from elephant ivory. These techniques are being used to assign geographic origin to poached ivory by comparing the ivory genotype to a geographic-based gene frequency map, developed separately. The method has three components: ivory pulverization, decalcification and DNA extraction. Pulverization occurs in a freezer mill while the sample is deep frozen in liquid nitrogen, preventing degradation of DNA during the process. Decalcification involves repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Besides taxonomy and population structure, the other major area in which genetics can contribute to African elephant conservation is in the geographic assignment of ivory samples [20], [21], [22], [23], [24], [26]. Current geographic assignment methods for elephants and ivory that use STRs may sometimes be imprecise or inaccurate (Figure 6) [7], [24], [25], [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides taxonomy and population structure, the other major area in which genetics can contribute to African elephant conservation is in the geographic assignment of ivory samples [20], [21], [22], [23], [24], [26]. Current geographic assignment methods for elephants and ivory that use STRs may sometimes be imprecise or inaccurate (Figure 6) [7], [24], [25], [26].…”
Section: Resultsmentioning
confidence: 99%
“…DNA has been successfully extracted from ivory [22], [23], while previous studies have shown that STR genotypes can be used to assign ivory to its geographic region of origin [20], [21], [24], [26]. However, previous studies have not attempted to rate each STR locus for its utility in assignment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies demonstrating the isolation and amplification of DNA from the known as well as confiscated ivory (9–12). The most interesting aspect of our work is that this is the first report for the isolation and amplification of DNA from the processed ivory material.…”
Section: Resultsmentioning
confidence: 99%
“…Only a very small amount of ivory powder is required to obtain a successful amplification (such as a tiny scraping that sits under the 20 μL PBS), being beneficial for processed or degraded ivory and also tiny invasive samples . The process of direct PCR required no DNA extraction step, making this protocol cost‐effective and less time consuming, compared to other previous reports . As the process required very little template it is possible to attempt direct‐PCR first and, if this is unsuccessful, then the extraction process can be attempted.…”
Section: Discussionmentioning
confidence: 99%